2022
DOI: 10.1021/acschemneuro.2c00593
|View full text |Cite
|
Sign up to set email alerts
|

Solution Nuclear Magnetic Resonance Structures of ATTTT and ATTTC Pentanucleotide Repeats Associated with SCA37 and FAMEs

Abstract: Expansions of ATTTT and ATTTC pentanucleotide repeats in the human genome are recently found to be associated with at least seven neurodegenerative diseases, including spinocerebellar ataxia type 37 (SCA37) and familial adult myoclonic epilepsy (FAME) types 1, 2, 3, 4, 6, and 7. The formation of non-B DNA structures during some biological processes is thought as a causative factor for repeat expansions. Yet, the structural basis for these pyrimidine-rich ATTTT and ATTTC repeat expansions remains elusive. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Li and Guo et al. recently reported the detailed structural characterization of DNA oligonucleotides with 3, 4 or 5 repeats of d(ATTTC) and found that they all adopt intramolecular minidumbbell ( 38 ). However, our results show that addition of Mg 2+ ions in up to physiologically relevant concentrations completely changes folding of d(ATTTC) 3 and leads to the formation of an unprecedented dimeric structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li and Guo et al. recently reported the detailed structural characterization of DNA oligonucleotides with 3, 4 or 5 repeats of d(ATTTC) and found that they all adopt intramolecular minidumbbell ( 38 ). However, our results show that addition of Mg 2+ ions in up to physiologically relevant concentrations completely changes folding of d(ATTTC) 3 and leads to the formation of an unprecedented dimeric structure.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, at least three repeats of d(ATTTC) are found in >100 coding regions of the human genome ( 34 ) that play important roles in a number of cellular processes, including transcriptional regulation, intracellular signalling, protein and membrane trafficking, chromatin remodelling, cell adhesion and neuronal migration, all of which go beyond the ‘original’ role in neurodegenerative diseases. Studying how these potentially pathogenic repeat insertions have arisen and how they are related to discoveries of new repeat expansion disorders have been advanced by structural information on minidumbbells, which were recently resolved at high resolution for d(ATTCT) n ( 35–37 ), d(ATTTT) n ( 38 ) and d(ATTTC) n . The partial topological similarities, like the arrangements of DNA backbone in minidumbbells and in pseudocircular G-hairpins ( 39 , 40 ), which are yet another class of recently discovered non-canonical structures, continues to incite the quest for understanding DNA folding beyond the primary sequence alone.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of ATTCT MDB provides an alternative pathway for repeat expansions in SCA10 apart from the replication re-initiation and template switching models [52] , [53] . Very recently, Li et al , have reported that the ATTTT/ATTTC repeats associated with SCA37 and FAMEs formed MDB structures [54] that are similar to the ATTCT MDB, further raising the potential biological significance of MDB structures.…”
Section: Mdb Structures Formed In Natural Pyrimidine-rich Repeatsmentioning
confidence: 99%